Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

What is ( √2 - √3 )² =

Sagot :

just use FOIL (First, Outer, Inner, Last).

( √2 - √3 ) X ( √2 - √3 )

First: √2 X √2 = 2
Outer: √2 X -√3 = -√6
Inner: -√3 X √2 = -√6
Last: -√3 X -√3 = 3

and then add them together.

2 - √6 - √6 + 3
5 - 2(√6)

The answer is 5 - 2(√6) . 

2-2(square root of 6)+ 3
=5-2(square root of 6)
or 0.1